STRATEGI PEMBELAJARAN ANAK USIA DINI DI TK TUNAS BANGSA KOTA BENGKULU - Retno Lara Ulani; Nova Novita; Alimni Dahlan (QALAM: JURNAL PENDIDIKAN ISLAM, 2024)
The problems found in the field are the learning strategies in early childhood education in early childhood education. The purpose of this research is to find out the forms of early childhood learning strategies. This type of research uses qualitative research with a descriptive approach, the data in the research is obtained through interviews, observation, and documentation. Qualitative research is research that intends to understand the phenomenon of what is experienced by the research subject. Based on the results of the research that early childhood learning strategies that learning strategies are needed so that the teaching and learning process in early childhood can be achieved optimally so that the expected goals are in accordance with what was planned. then at least five criteria are needed that must be met in the learning model or learning development, namely: 1) having goals; 2) compatibility with goals; 3) systematic; 4) have evaluation activities; and 5) fun. The learning strategy is in the form of direct learning through learning while playing.Keywords: Strategy, Learning, early childhood.